2024
DOI: 10.3390/s24103013
|View full text |Cite
|
Sign up to set email alerts
|

1 V Tunable High-Quality Universal Filter Using Multiple-Input Operational Transconductance Amplifiers

Montree Kumngern,
Fabian Khateb,
Tomasz Kulej
et al.

Abstract: This paper presents a new multiple-input single-output voltage-mode universal filter employing four multiple-input operational transconductance amplifiers (MI-OTAs) and three grounded capacitors suitable for low-voltage low-frequency applications. The quality factor (Q) of the filter functions can be tuned by both the capacitance ratio and the transconductance ratio. The multiple inputs of the OTA are realized using the bulk-driven multiple-input MOS transistor technique. The MI-OTA-based filter can also offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…Figures 4 to 8 demonstrate that the voltage gain achieved with the WCA is 98.63 dB, representing a 24.4% increase compared to the previous value of 79.29 dB without utilizing the WCA. In the study [8], the voltage gain is reported as 56.11 dB, while in the study [22], it is stated as 53.9 dB. Additionally, the Gain Bandwidth (GB) is significantly improved with the WCA, reaching 300.5 MHz, which is improve the previous value of 47.8 MHz.…”
Section: Simulation Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Figures 4 to 8 demonstrate that the voltage gain achieved with the WCA is 98.63 dB, representing a 24.4% increase compared to the previous value of 79.29 dB without utilizing the WCA. In the study [8], the voltage gain is reported as 56.11 dB, while in the study [22], it is stated as 53.9 dB. Additionally, the Gain Bandwidth (GB) is significantly improved with the WCA, reaching 300.5 MHz, which is improve the previous value of 47.8 MHz.…”
Section: Simulation Resultsmentioning
confidence: 82%
“…The power dissipation of the optimized design is reduced by 15.5%, decreasing from 255.6 μW to 216 μW after applying the WCA. In the study [8], the power dissipation is reported as 6.106 μW, while in the study [22], it is noted as 1100 μW and in the study [23], it is state as 540 μW. Moreover, other parameters such as CMRR and settling time (ts) also exhibit improvements through the use of the Water Cycle Algorithm, For temperature influence, this design is room temperatures and note the results are among the acceptable Ring compared to other research as in Table 4.…”
Section: Simulation Resultsmentioning
confidence: 96%
See 1 more Smart Citation